Perluasan Makna Nomina Bahasa Indonesia dalam Novel - Fathia Roifah; Nguman Abdul Manaf (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research is based on the phenomenon of language development. This development results in language changes both in terms of words and meanings. This study aims to explain Indonesian nouns that experience meaning expansion in novels and explain the factors that cause the expansion of the meaning of Indonesian nouns in novels. This research uses a descriptive qualitative method. The data source of this research is novels from several authors, namely "Bilangan Fu" by Ayu Utami, "Ayah dan Laskar Pelangi" by Andrea Hirata, "Sedang Tuhan pun Cemburu" by Emha Ainun Nadjib, "Ranah 3 Warna" by A. Fuadi, "Yang Fana adalah Waktu" by Sapardi Djoko Damono, "Laut Bercerita" by Leila S. Chudori, "Autumn in Paris" by Ilana Tan, "Cantik itu Luka" by Eka Kurniawan, and "Supernova" by Dea Lestari. This research results in the discovery of 15 basic nouns and 12 derivative nouns that experience the expansion of meaning in Indonesian. Meanwhile, the factors that cause the expansion of meaning are the development of science and technology, socio-cultural development, differences in the field of use, association, and term development.